Pengembangan Media Pembelajaran Sparkol Videoscribe untuk Meningkatkan Keterampilan Menulis Deskripsi di Kelas V SD Negeri 066650 Kota Medan T.A 2023/2024 - Lubis, Raisyah Aulia Nabila; Faisal; Simanjuntak, Eva Betty; Halimatussakdiah; Fajar Sidik Siregar; Ermansyah; Elviana Santi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research uses the ADDIE development model to develop sparkol videoscribe learning media on the description text material for grade V students at SD Negeri 066650 Medan City in the even semester of the 2023/2024 academic year. This research involved 23 class V students as research subjects, 2 expert validations with the aim of testing the validity of sparkol videoscribe learning media and 1 teacher to test the practicality of sparkol videoscribe learning media in Indonesian language subjects in the independent curriculum. Validation by material experts and media design experts showed that this sparkol videoscribe learning media scored high, material experts gave a score of 83 from a maximum score of 100 with a percentage (83%) and a media design expert gave a score of 174 from a maximum score of 180 with a percentage (96.66%). The teacher also gave a high score for the practicality test with a score of 53 from a mascsimal score of 55 with a percentage (96.36%), with all aspects such as appearance, presentation, material, and language getting the categories "very decent" and "very valid". The evaluation results show a significant improvement in the learning results of students seen from the comparison of pretest and post-test scores of students, the pre-test result score is 60.17 while the posttest result score reaches 85.13 with an increase of 24.96. It can be concluded that the videoscribe learning media sparkol is "very feasible" to be used as a learning medium in Indonesian language learning and can improve students' writing skills.